I marchi di fabbrica sulla ceramica a vernice nera padana tra la tarda repubblica e la prima età imperiale - Mantovani, Valentina (Rei Cretariae Romanae Fautorum Acta, 2024)
This paper presents preliminary results of the updated catalogue of Roman Black-Gloss Pottery of the Po Valley with stamps. To date, several attempts have been made to collect evidence of marks on black-glazed ceramics, focusing on different production areas, without being able to produce a complete corpus. The research, carried out on published and unpublished material, has identified 97 marks in planta pedis, with rectangular, circular and hides frames, distributed throughout the Po Valley, from Cuneo to Aquileia, and in Noricum. The study significantly increases the number of quantitative data. It also provides a more detailed knowledge of the forms used for marking, and highlights the chronological margins of the phenomenon in the Po Valley area. Still completely unknown are the production sites: in fact, the kilns have not yet been discovered. However, the several archaeological analyses provide some clues, and in the future, this will certainly have to be further investigated.